Analisis persediaan dengan Economic Order Quantity di UMKM Kacang Atom di Tanah Datar, Sumatera Barat - Marlina, Winny; Sarahita, Venia Dwi Ayu; Febriyanti , Rizka (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
MSME GDR peanuts are one of the MSMEs in Tanah Datar, West Sumatra. The surge in production and product demand in the market has created challenges for these MSMEs, and they are experiencing difficulties in determining the amount of raw material supply or inventory needed. This research aims to calculate the inventory of GDR Nuts, determine what factors influence inventory planning in GDR Nut MSMEs, and calculate the amount of safety stock and ROP. The method used to overcome this problem is the EOQ (Economic Order Quantity) method to determine economic purchases for Nut MSMEs. The data processing and analysis results show that the ordering of raw material supplies in GDR MSMEs was 1.6 times with order results of 92,156 kg using the EOQ method. The leading cause of this inventory problem is the need for more implementation of effective operational management and inaccuracies in inventory calculations. As a result, there is often a need for more raw materials. To overcome this, GDR MSMEs have a safety stock of 977.3 kg and a reorder point of 13,153 times.